Comparison of Skull Size in Sympatric and Allopatric Fishers (Martes pennanti) and American Martens (Martes americana) - Brandt, Matthew; Davis, Miranda; Harrington, Tom; Schultz, Eric (Digital Commons @ UConn, 2019)
Interactions between two species with similar ranges may cause character displacement, especially if the two species are closely related. There is little research regarding character displacement between two related mammal species. American martens (Martes americana) and fishers (M. pennanti) are closely related and have some range overlap. I hypothesized that American martens would be smaller in size in locations where they are sympatric to fishers compared to allopatric locations. Also, I hypothesized that fishers would be larger in sympatric locations compared to their allopatric counterparts. To test these hypotheses, I compared the skull sizes of American marten and fisher specimens from locations that were either allopatric or sympatric for both species. The condylobasal length was used to measure the size of each skull. Fisher and marten skulls of both sexes that were found in sympatric locations were, on average, smaller than the skulls from allopatric locations. These differences could be a result of interspecific competition and range overlap between not just fishers and martens, but of other larger carnivores not considered in this study. Fishers and martens could be affecting the average body size of each other’s species via interspecific competition. A larger sample size of both species’ skulls from more localities could further support these findings.